Automated Piston Gauge Calibration System. Issue 1 (3rd April 2018) - Scherschligt, Julia; Cross, Christina D.; Quintavalle, John; Yang, Yuanchao; Driver, R. Gregory; Schlatter, Katie; Olson, Douglas A.
Abstract: Piston gauges or pressure balances are important primary standards for the realization of the SI unit of pressure, the pascal. Because of their long-term stability, they are also used as secondary or working standards in the dissemination of the pressure scale. The National Institute of Standards and Technology (NIST) operates and maintains a calibration service for these devices, and has recently undertaken a modernization effort. Following a preliminary investigation into the feasibility of using transducers as instantaneous in-situ transfer standards, we now present the results of a near fully automated calibration system. This effort includes the design, building, and validation of an automated gas-handling manifold, and the development of a new software suite. The new system demonstrates an expanded uncertainty on the order of 1 in 10 5, comparable to the traditional system, but offers a five-fold decrease in calibration turnaround time.